Hijab, Workplace Discrimination, and Organizational Accommodation: A Systematic Literature Review on Intersectionality, Multicultural Policies, and Advocacy - Huda, Khoirul; Djono, D (Universitas Syiah Kuala, 2025)
This article presents a systematic literature review of hijab, discrimination, and organizational accommodation in workplaces across North America, Europe, Asia, and Australia between 2016 and 2025. The review aimed to synthesize empirical and conceptual studies to understand how visible religious identity intersects with organizational culture, legal frameworks, and socio-political dynamics. Following PRISMA guidelines, searches were conducted using Scopus with keywords related to hijab, multiculturalism, tolerance, discrimination. The results highlight four thematic areas public attitudes, multicultural policies, and acceptance of visible religious identity; organizational and institutional accommodation between legal norms and implementation; discursive and political mechanisms normalizing intolerance; and advocacy architectures and cross-issue comparisons. Findings show that hijabi women face structural and intersectional discrimination influenced by national identity, Islamophobia, and stigma. Implementation gaps persist despite legal mandates, while extremist and populist rhetoric exacerbate resistance to accommodation. However, advocacy coalitions, media literacy programs, and context-sensitive HR strategies offer pathways to strengthen inclusivity. The review concludes that hijab-related workplace discrimination cannot be fully understood through single-identity frameworks; instead, intersectionality, stigma theory, and reasonable accommodation provide robust lenses for analysis.